Assessment of wild-animal crop raiding and it’s influence on wildlife conservation around Kainji Lake National Park, Nigeria - Yaduma, Z B; Halidu, S K; Adelakun, K M; Olakunle, S D; Mohammed, N (Journal of Biodiversity Conservation and Bioresource Management, 2024)
This study examined the influence of wild animal crop raiding on wildlife conservation around Kainji Lake National Park, Nigeria. 150 questionnaires were administered to the affected farmers in the villages with farmland within 2 km of the park. The results show that the major occupation in the study area is farming, and 92% of the farmers affirmed frequent raiding of farmed crops, such as maize, rice, sorghum, millet, groundnut, beans, and yam by birds, baboons, monkeys, and rodents. The preventive measures adopted by the farmers include scarecrow (41.33%), watch guarding (20.67%), and trapping (16.67%). It was further confirmed by the majority (mean= 4.65±0.50) of respondents that incidents of crop raiding are a threat to the means of livelihood of affected farmers and consequently contribute to the unemployment menace in the study area. Respondents (mean= 3.83±0.43) confirmed the killing of the marauding wild animal whenever it is spotted to avoid future damage to their farm products. However, this study established from the farmers’ opinion that a major benefit attributed to compensation programs may increase the tolerance of wildlife and promote more positive attitudes and support for conservation among the local communities’. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 45-58